2014
DOI: 10.1186/s40201-014-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dust storm events on emergency admissions for cardiovascular and respiratory diseases in Sanandaj, Iran

Abstract: BackgroundIn recent years, increasing dust storms from western neighboring countries of Iran influenced western and central parts of the country. In this case, level of concentration of atmospheric particulate matter greater than 10 μm (PM10) remained higher for several days compared to the levels before the event. Accordingly, Suspended particulate matters of dust storms in western Iran have caused PM10 pollution in Sanandaj (capital of the Iranian province of Kurdistan) and other Iranian cities. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The study by Ebrahimzadeh et al also showed that by every 110 µg increase of air pollutant in a cubic meter of air, there will be an increase of 1.35% and 0.021%, respectively, in the incidence of cardiac and respiratory illnesses in Sanandaj [12]. Studies by Pan et al showed significant relationship between storms of dust and particulate matter with increase in hospital admissions [13].…”
Section: Discussionmentioning
confidence: 96%
“…The study by Ebrahimzadeh et al also showed that by every 110 µg increase of air pollutant in a cubic meter of air, there will be an increase of 1.35% and 0.021%, respectively, in the incidence of cardiac and respiratory illnesses in Sanandaj [12]. Studies by Pan et al showed significant relationship between storms of dust and particulate matter with increase in hospital admissions [13].…”
Section: Discussionmentioning
confidence: 96%
“…The average PM 10 concentrations during dust episodes in Sanandaj (187 µg m -3 ) were significantly higher than on other days (48.7 µg m -3 ) (Ebrahimi et al, 2014). According to WHO's database, the annual average PM 2.5 concentrations in Ahvaz and Sanandaj during 2010 were 95 and 41 µg m -3 , respectively (WHO, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The areas are also faced with ambient air pollution from dust storms. The simultaneous exposure to indoor and outdoor air pollution can cause synergistic health effects (Ebrahimi et al, 2014;Rashki et al, 2012;Shahsavani et al, 2012).…”
Section: Spatiotemporal Trendmentioning
confidence: 99%